1997
DOI: 10.5144/0256-4947.1997.170
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension in Saudi Arabia

Abstract: A cross-sectional population-based survey employing a cluster sampling method and household visits by trained health teams investigated hypertension prevalence in the Kingdom among 13,700 individuals of both sexes in all age groups. The World Health Organization (WHO) definition of hypertension of ∫ 160/95 mmHg was used; it was found that 9.1% and 8.7% of the total sample investigated were systolic and diastolic hypertensives, respectively. However, 12.4% and 7.9% of children younger than 18 years were systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
219
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(261 citation statements)
references
References 17 publications
35
219
7
Order By: Relevance
“…Similar to other studies, 21,24,26 our results demonstrated that hypertension was more prevalent among women than men and increased with age for both genders, though the increase was more pronounced among women than men. Hormonal factors, postmenopausal weight gain, and a different risk profile might account for the higher age-specific prevalence rates of hypertension among women compared with men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies, 21,24,26 our results demonstrated that hypertension was more prevalent among women than men and increased with age for both genders, though the increase was more pronounced among women than men. Hormonal factors, postmenopausal weight gain, and a different risk profile might account for the higher age-specific prevalence rates of hypertension among women compared with men.…”
Section: Discussionsupporting
confidence: 91%
“…This rate exceeds that reported in other developing countries in the region (for example, Egypt (26.3%), Cameroon (15%), Ghana (29.4%)), [21][22][23] as well as that reported in developed countries in Asia (for example, China (20%), Pakistan (20.7%), Saudi Arabia (26.1%), Malaysia (27.8%)). [24][25][26][27] The rate remains lower than that in the developed countries of Europe (for example, Italy (38%), United Kingdom (42%), Spain (47%), Romania (44.9%), Germany (55%)) and the United States (56%)). 28,29 Our findings further substantiate the results of sustained and integrated economical, social and health development in Tunisia.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies on the prevalence of hypertension in KSA have demonstrated persistently increasing figures [28]. Several reasons such as lifestyle change in KSA towards urbanization and adopting new dietary habits, are likely to result in hypertension and increasing prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the increasing incidence of atherosclerotic risk factors in the Saudi population [2] . Obesity and overweight prevalence are exceeding 35.5% [2,3] , adult onset diabetes affecting at least 24% [2,4] , and hypertension in about 26% [2,5] . The prevalence of coronary artery disease among hypertensive patients is about 8.2% [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and overweight prevalence are exceeding 35.5% [2,3] , adult onset diabetes affecting at least 24% [2,4] , and hypertension in about 26% [2,5] . The prevalence of coronary artery disease among hypertensive patients is about 8.2% [5] . The dramatic increase of hypercholesterolemia, affecting about 45% of the Saudi population is secondary to change in life style and food habits [2,3] .…”
Section: Discussionmentioning
confidence: 99%